2016
DOI: 10.16986/huje.2016017558
|View full text |Cite
|
Sign up to set email alerts
|

EFL Learners Use of Formulaic Language in Oral Assessments: A Study on Fluency and Proficiency

Abstract: Despite the recent, increasing interest in the research of formulaic language which constitutes a significant part of languages, there is little research on formulaic language use in registers such as classroom teaching and textbooks. Therefore, this article aims to investigate a) formulaic language use of EFL learners in multi-task oral proficiency exams consisting of an individual and a paired task, b) the task type in which these learners use more formulaic language, and c) whether the use of formulaic expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 52 publications
0
12
0
1
Order By: Relevance
“…Highlighting the role of formulaic expressions in vocabulary and language learning, Mutlu & Kaşlıoğlu's (2016) study involving 326 EFL learners studying at five high schools revealed a positive relationship between vocabulary size and receptive and productive knowledge of collocations. Turkish EFL learners’ use of formulaic language in oral proficiency exams has been found to be correlated with the task type as well as their fluency and overall language proficiency scores (Üstünbaş & Ortaçtepe 2016). In order to examine the use of lexical bundles, Öztürk & Durmuşoğlu-Köse (2016) compiled a corpus of 150 texts containing both Turkish and native English postgraduate students’ M.A.…”
Section: English Language Learning and Language Learnersmentioning
confidence: 99%
“…Highlighting the role of formulaic expressions in vocabulary and language learning, Mutlu & Kaşlıoğlu's (2016) study involving 326 EFL learners studying at five high schools revealed a positive relationship between vocabulary size and receptive and productive knowledge of collocations. Turkish EFL learners’ use of formulaic language in oral proficiency exams has been found to be correlated with the task type as well as their fluency and overall language proficiency scores (Üstünbaş & Ortaçtepe 2016). In order to examine the use of lexical bundles, Öztürk & Durmuşoğlu-Köse (2016) compiled a corpus of 150 texts containing both Turkish and native English postgraduate students’ M.A.…”
Section: English Language Learning and Language Learnersmentioning
confidence: 99%
“…Overall, there are ten articles that state that teachers have challenges with cultural or context differences found in textbooks (Abdul Abdul Aziz & Makhtar, 2021;Calafato, 2021;Gopal, Maniam & Nallaluthan, 2023;Lukas et al, 2020;Oi, 2018). Five articles state the challenges of teachers in the diversity in abilities and language level of the students (Calafato & Simmonds (2022); Gopal, Maniam & Nallaluthan (2023); Oi (2018); Towns (2020); Ustunbas & Ortactepe, (2016) and two articles stating time constraints as a challenge for teachers in using CEFR-Aligned English textbooks (Calafato (2021); Towns ( 2020)). Based on this thematic analysis, it can be concluded that all articles have at least one similarity in each theme and sub-theme that has been identified.…”
Section: Findings and Analysismentioning
confidence: 99%
“…The literature includes a large number of studies conducted on formulaic expressions which, for instance, show a correlation observed between students' fluency, overall proficiency scores, and their utilization of formulaic expressions (Üstünbaş & Ortaçtepe, 2016); dealing with the syntactic and functional analysis of formulaic expressions in learners' written outputs (Allen, 2010); bringing together the most frequent collocations of spoken English (Shin & Nation, 2007); investigating semantically opaque formulaic expressions in textbooks (Hsu, 2014); examining structural and functional features of lexical bundles (Bal-Gezegin, 2019;Güngör & Uysal, 2016;Hyland, 2008); comparing the lexical bundle use of academics with those of learners (Cortes, 2004); and analyzing the use of lexical bundles in the articles of a specific academic discipline in two different languages (Cortes, 2008). Üstünbaş and Ortaçtepe (2016) examined students' use of formulaic expressions in oral proficiency exam. Examining the effects of different task types on the use of formulaic expressions, Üstünbaş and Ortaçtepe (2016) also analyzed the relationship between students' use of formulaic expressions and fluency and overall scores in oral proficiency exam.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Üstünbaş and Ortaçtepe (2016) examined students' use of formulaic expressions in oral proficiency exam. Examining the effects of different task types on the use of formulaic expressions, Üstünbaş and Ortaçtepe (2016) also analyzed the relationship between students' use of formulaic expressions and fluency and overall scores in oral proficiency exam. The researchers made content analyses of the textbook the students used throughout the semester and of the spoken discourse of students' oral examinations in terms of the use of formulaic expressions based on Kecskes' formulaic continuum (2007).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation